Wireless Multi-group Multicast Precoding with Selective RF Energy Harvesting - Gautam, Sumit; Lagunas, Eva; Chatzinotas, Symeon; Ottersten, Bjorn (2019 27th European Signal Processing Conference (EUSIPCO), 2019)
We present a novel framework for multi-group multicast precoding in the presence of three types of wireless users which are distributed among various multicast groups. A multi-antenna transmitter conveys information and/or energy to the groups of corresponding receivers using more than one multicast streams. The information specific users have conventional receiver architectures to process data, energy harvesting users collect energy using the non-linear energy harvesting module and each of the joint information decoding and energy harvesting capable user is assumed to employ the separated architecture with disparate non-linear energy harvesting and conventional information decoding units. In this context, we formulate and analyze the problem of total transmit power minimization for optimal precoder design subjected to minimum signal-to-interference-and-noise ratio and harvested energy demands at the respective users under three different scenarios. This problem is solved via semi-definite relaxation and the advantages of employing separate information and energy precoders are shown over joint and per-user information and energy precoder designs. Simulation results illustrate the benefits of proposed framework under several operating conditions and parameter values.